An Analysis of Floating Maxim of Hotel Transylvania 2 Movie: English - Hastuti Retno Kuspiyah; Tika Padmila; Erni Yulianingsih; Wardatul Mauludiyah; Deny Syehtrianto (Journal of English Development, 2024)
Abstract The title of this research is to analyze types of floating maxim. This research described   the  types  of  maxims  that  are  flouted  by all characters in Hotel Transylvania 2 movie. This research was descriptive research, and the data sources of this research was Hotel Transylvania 2 movie and supported by pragmatics theory related to the movie to increase and add to the theory of floating maxim. The researcher used documentation as collecting data techniques. The descriptive data was gotten from words, sentences, or picture in every action in the movie. After viewing and comprehending the film, the researcher looked for the script, rewatched it, and read the dialogue transcript. She then chose and categorized the utterances in the film that demonstrated maxim flouting, collecting all of the information into a data sheet. These results in the following consequences: the floating maxims of quantity, quality, relation, and manner. The most common type of flouting maxim in the movie, in terms of occurrence, is the quantity maxim. The relational maxim comes in second, the manner maxim comes in third, and the quality maxim appears in last.